Impact analysis of change in component reliabilities in safety-critical systems - Singh P.; Singh L. (My University, 2025)
A safety-critical system or life-critical system is a system whose failure or malfunction may result in one (or more) of the following outcomes: death or serious injury to people and loss or severe damage to equipment/property. Such systems are very common in nuclear power plants and are composed of several components, performing different functions. The criticality of these components is ranked according to the criticality of the functions they perform. Therefore, the impact of component failure on system will be different for different components. It is essential to determine the impact of failure of any component on overall system to take preventive and corrective actions. This paper proposes a technique to determine the criticality of the components for their impact on the overall system using Bayesian approach. The theoretical basis and effectiveness of the proposed technique is shown and validated on a real case study of a nuclear power plant system. © 2019 John Wiley & Sons, Ltd.